You've been chosen : thriving through the unexpected - Marshall, Cynthia, 1959- (Ballantine Books, 2022)
"A relentlessly optimistic memoir by one of the most influential Black business leaders in America today, offering hope and practical guidance for navigating life's most difficult challenges, inspired by the author's cancer journal that went viral "Focus. Pray. Act. Serve. And we'll get through this together." Cynthia "Cynt" Marshall has spent her life beating the odds. Growing up in the public housing projects of Richmond, California, Cynt never wondered why her mother didn't sit down to dinner every night, realizing only later that she sometimes sacrificed her own meal so her six children could eat. Cynt's father, meanwhile, had a terrifying temper and physically abused his wife and children for years. But Cynt didn't let her background deter her. Instead, she focused on her education, propelling herself through college and into her first job in corporate America. As a rising professional, Cynt overcame overt and subtle racism to become one of the first Black, female officers at AT&T by age forty, while surviving multiple miscarriages and family tragedies. As her husband helped her see a new way of creating a family, she started to see that her plan was not always God's plan. Cynt was president of AT&T North Carolina when, at fifty-one, she was diagnosed with Stage 3 colon cancer, just one lymph node from Stage 4. Overnight, her life changed from managing corporate strategy to managing an aggressive chemotherapy schedule, her best hope for survival. Instead of giving up, Cynt got on her knees. Her lifelong spiritual foundation and faith in the power of prayer carried her forward as she shared her journey online through heartfelt posts that chronicled the challenges and unexpected blessings of cancer, transforming her diagnosis from a death sentence into a chance to serve people around the world. With positivity and deep faith, Cynt Marshall reminds us that we are each uniquely equipped for the challenges life presents us. In sharing her deeply inspiring story, she helps ensure that we will not just survive but thrive through trials, celebrate challenges, and laugh at what life brings us"--Provided by publisher.